An overview of MANETs: applications, characteristics, challenges and recent issues - Ahmed, Diaa Eldein Mustafa; Khalifa, Othman Omran (Blue Eyes Intelligence Engineering & Sciences Publication Pvt. Ltd, 2017)
In recent years, due to emerging technologies in the field of wireless networks, ad hoc networks have attracted much attention from the research community and industry since has important technical advances have arisen as a consequence. Mobile ad-hoc Networks (MANETs) is a group of self-organized and self-configured wireless mobile nodes (MNs) such as mobile devices, laptops ,and PDAs , able to communicate with each other without the need of any neither fixed network infrastructure nor centralized administrative support. MANET is a network that exchanges information among the entities that are potentially mobile without any pre-defined infrastructure based communication support. These networks are of practical importance in applications like environmental monitoring, health care, military, location tracking, disaster recovery and many more. This paper provides a comprehensive study of MANETs applications scenarios, main features and characteristics, challenges facing the deployment of MANET, current issues and latest research issues